GenAI Role in Redefining Learning and Skilling in Companies - Hamburg, I. (European Journal of Applied Sciences, 2026)
Gen AI models are growing rapidly, changing job roles, and revolutionizing entire industries. Due to advances in technologies, particularly generative AI (GenAI), which also transform industrial processes, companies need to adopt a human-centric approach to corresponding implementation that empowers employees and supports clients. This should be done, i.e., through upskilling, reskilling, cross-skilling, and learning initiatives. GenAI and the future of work and education are strongly connected. GenAI supports learning and development by performing various tasks that influence creating and interacting with content, One problem within companies is the assessment and development of employees’ skills, as traditional methods often fail to provide real-time feedback. GenAI supports skill assessment tools for continuous, granular evaluations of employees’ abilities. Through continuous learning, including lifelong learning, and fostering a culture of innovation, businesses can use the full potential of GenAI, ensuring growth, efficiency, and that employees are equipped with the technical skills needed to succeed in an AI-enhanced world. Using a suitable approach to skill development and a commitment to continuous learning within organizations, GenAI drives innovation, improves decision-making, and creates new growth opportunities. In this paper, we first outline some useful steps to realize the value of GenAI transformation and facilitate GenAI adoption in companies. Then, it is briefly explained how GenAI supports employees’ development, offering a transformative approach to addressing challenges through learning, unlearning, and relearning, thereby maximizing the opportunities inherent in lifelong learning. Besides lifelong learning, the workforce should be prepared for these changes through skilling programs. In this context, different forms of skilling, like upskilling, reskilling, and cross-skilling, are presented. The results of this paper are based on a literature recherche, an analysis of individual tasks across different occupations, also done within Erasmus+ projects, and discussions with trainers/educators. In conclusion, with a suitable approach to skill development and a commitment to continuous learning within organizations, GenAI drives innovation, enhances decision-making, and creates new opportunities.